Faktor-Faktor Yang Mempengaruhi Kunjungan Antenatal Care Terhadap Perilaku Antenatal Care - Puji Astuti Wiratmo; Lisnadiyanti; Nurkamilia Sopianah (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2020)
Introduction: Antenatal Care (ANC) is an effort to detect the occurrence of high risk in pregnant women. However, ANC non-compliance was still found due to several factors. Aim of study: This study aims to determine factors that influence ANC visits to ANC behavior at Puskesmas Pasar Rebo East Jakarta. Method: This study used a descriptive correlation design with a cross-sectional survey. Data analysis used Spearman's rho with 117 respondents. Results and Discussion: The results showed that there are some factors that influence ANC visits to ANC behavior, including age with a correlation value (r = 0.419), a p-value of 0.000; education with a correlation value (r = 0.425), p-value of 0.000; jobs with a correlation value (r = 0.279), p-value of 0.002; income with a correlation value (r = 0.407), p-value of 0.000; knowledge with a correlation value (r = 0.409), p-value of 0.000; husband / family support with a correlation value (r = 0.417), p-value of 0.000; attitude with a correlation value (r = 0.597), p-value of 0.000 (<0.05). Irregularity in carrying out ANC has a bad impact on pregnant women because they are not aware of the risk factors that may occur to the mother and her fetus and can not be detected early on the disease suffered by pregnant women. Conclusion: The conclusion of this study is nurses as health workers need to increase their role as educators and health care provider to pregnant women and their families about the importance of ANC to reduce maternal mortality and monitor the state of the fetus.